2013
DOI: 10.1016/j.rasd.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in autism spectrum disorder: A literature review

Abstract: Comorbidity is defined as the co-occurrence of two or more disorders in the same person (Matson & Nebel-Schwalm, 2007). The current study provides a review of the literature on comorbidity, in relation to comorbid psychiatric and medical disorders in babies and infants, children, adults and across the lifespan. We also examine comorbid conditions such as attention deficit/hyperactivity disorder (AD/HD), epilepsy, gastrointestinal symptoms, sleep problems, feeding problems and toileting problems in individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(138 citation statements)
references
References 108 publications
4
126
1
7
Order By: Relevance
“…Evidence is growing that anxiety disorder is common in individuals with ASD, especially among those with Asperger's and high-functioning ASD (Hillier et al 2007b;Mannion and Leader 2013). Kuusikko et al (2008) found that anxiety disorder increased as individuals with ASD became older, while the typically developing adolescents reported a decrease of anxiety.…”
Section: Internal Challenging Factorsmentioning
confidence: 99%
“…Evidence is growing that anxiety disorder is common in individuals with ASD, especially among those with Asperger's and high-functioning ASD (Hillier et al 2007b;Mannion and Leader 2013). Kuusikko et al (2008) found that anxiety disorder increased as individuals with ASD became older, while the typically developing adolescents reported a decrease of anxiety.…”
Section: Internal Challenging Factorsmentioning
confidence: 99%
“…Taken together, a great deal of evidence lends itself to promoting the CBCL and CBCL 1-5 as effective screeners in distinguishing between ASD and other diagnostic presentations (e.g., [14,18,[21][22][23]25]); however, given the myriad of comorbid problems associated with ASD, including but not limited to ADHD, anxiety, depression, feeding concerns, and sleep issues [25], it is essential that the effectiveness of measures at differentiating between individuals with ASD alone and those with ASD and comorbid symptoms also is evaluated. In light of this, researchers found the CBCL 1-5 to be effective at distinguishing between children with ASD with an emotional and behavioral disorder (EBD) and children with ASD without comorbid EBD [26].…”
Section: Identifying Asd and Comorbid Symptomsmentioning
confidence: 99%
“…Recent research has demonstrated how Attention-deficit/hyperactivity disorder (AD/HD) in autism spectrum disorder (ASD) is becoming a highly researched area in the field of comorbidity research (Matson & Williams, in press;Mannion & Leader, 2013). Matson, Rieske, and Williams (2013) provided a thorough review on the relationship between autism spectrum disorders (ASD) and AD/HD.…”
Section: Introductionmentioning
confidence: 99%